Design and assembly of a novel asymmetric supercapacitor based on all-metal selenides electrodes. (10th December 2020) - Lei, Haikuo; Zhou, Jiezi; Zhao, Rui; Peng, Hui; Xu, Yipu; Wang, Faqiang; Hamouda, Hamouda Adam; Zhang, Wenxu; Ma, Guofu
Highlights: Ni, Co bimetallic selenides microspheres and BiSe nanosheets are synthesized. The (Ni, Co)Se2 demonstrate enhanced capacitive performances than pure NiSe2 and CoSe2 . A novel asymmetric supercapacitor based on all-metal selenides electrodes is proposed. (Ni, Co)Se2 //BiSe ASC possesses extended operating voltage and high energy density. Abstract: Transition metal chalcogenides (TMCs) are considered as one of the most promising electrode materials for energy storage and conversion due to their unique intrinsic properties, but their electrochemical performance is largely limited by its poor conductivity. Thus, it is a feasible strategy to develop TMCs with hierarchical and ordered nanostructure to guide the electronic transport ways thereby enhance the electrical conductivity. Herein, a facile one-step solvothermal method has been designed and employed to synthesize uniform Ni, Co bimetallic selenides (termed as (Ni, Co)Se2 ) microspheres and BiSe nanosheets. The (Ni, Co)Se2 demonstrate enhanced capacitive performances of 106 mAh g −1 at 1 A g −1, which are more than two times of pure NiSe2 and five times of pure CoSe2 at the same current densities. Similarly, the BiSe nanosheets also exhibits a high specific capacity of 104 mAh g −1 at 1 A g −1 and good rate capability. Interestingly, a novel asymmetric supercapacitor is fabricated by using (Ni, Co)Se2 nanospheres as the positive electrode and BiSe nanosheets as the negative electrode, which possesses extended operating voltage of 1.65 V, high energy density of 34.4 Wh·kg −1 at a power density of 373 W·kg −1, and an acceptable cycling stability of 85% capacity retention after 5000 cycles. Graphical abstract: A facile one-step solvothermal method has been designed and employed to synthesize uniform (Ni, Co)Se2 microspheres and BiSe nanosheets. Based on high electrochemical properties and complementary operating voltage of (Ni, Co)Se2 and BiSe materials, a novel (Ni, Co)Se2 //BiSe asymmetric supercapacitor is fabricated from both metal selenides, which possesses extended operating voltage, high energy density, and good cycling stability. Image, graphical abstract